Biobanking of Dehydrated Human Donor Corneal Stroma to Increase the Supply of Anterior Lamellar Grafts. Issue 4 (April 2019) - Romano, Vito; Levis, Hannah J.; Gallon, Paola; Lace, Rebecca; Borroni, Davide; Ponzin, Diego; Ruzza, Alessandro; Kaye, Stephen B.; Ferrari, Stefano; Parekh, Mohit
Abstract : Purpose: To investigate the effect of dehydration on human donor corneal stroma for biobanking. Methods: Epithelium and endothelium of research-grade human donor corneas (n = 12) were scraped off, leaving a bare stroma with attached sclera. The tissues were placed in a large Petri dish prefilled with silica gel in the periphery and stored at room temperature for 14 days. At the end of preservation, the tissues were rehydrated by being submerged in phosphate-buffered saline for 15 minutes. Transparency (using a custom-built device) and thickness (using optical coherence tomography) measurements were recorded before dehydration, after dehydration, and after rehydration of the tissues. Periodic acid-Schiff and alpha-smooth muscle actin (α-SMA) staining before dehydration and after rehydration were performed to determine the presence of keratocytes and expression of α-SMA. Tensile stress-strain before dehydration and after rehydration was performed to evaluate the biomechanical properties. Results: No difference in corneal transparency before dehydration (69.57 ± 6.41%) and after rehydration (67.37 ± 2.82%), P = 0.36, was observed. The corneas were more compact after dehydration. A significant change in thickness between before dehydration (625.8 ± 75.58 μm) and after rehydration (563.6 ± 15.77 μm) stage, P = 0.03, was noticed. The thickness was reduced to 147.6 ± 3.71 μm when dehydrated. Periodic acid-Schiff staining showed presence of stromal keratocytes and α-SMA protein expressed in control, dehydrated, and rehydrated corneas. There was no significant difference in the stiffness between control (27.86 ± 11.65 MPa) and rehydrated corneas (31.46 ± 11.41 MPa). Conclusions: Human donor corneal stroma can be biobanked for up to 2 weeks in a dehydrated condition without losing their molecular or biomechanical properties after rehydration. Abstract : Supplemental Digital Content is Available in the Text.